A botanical daughter - Medlock, Noah (Titan Books, 2024)
"It is an unusual thing, to live in a botanical garden. But Simon and Gregor are an unusual pair of gentlemen. Hidden away in their glass sanctuary from the disapproving tattle of Victorian London, they are free to follow their own interests without interference. For Simon, this means long hours in the dark basement workshop, working his taxidermical art. Gregor's business is exotic plants - lucrative, but harmless enough. Until his latest acquisition, a strange fungus which shows signs of intellect beyond any plant he's seen, inspires him to attempt a masterwork: true intelligent life from plant matter. Driven by the glory he'll earn from the Royal Horticultural Society for such an achievement, Gregor ignores the flaws in his plan: that intelligence cannot be controlled; that plants cannot be reasoned with; and that the only way his plant-beast will flourish is if he uses a recently deceased corpse for the substrate. The experiment - or Chloe, as she is named - outstrips even Gregor's expectations, entangling their strange household. But as Gregor's experiment flourishes, he wilts under the cost of keeping it hidden from jealous eyes. The mycelium grows apace in this sultry greenhouse. But who is cultivating whom?"--